2004
DOI: 10.1093/pcp/pch125
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Phytochrome Interacting Factor 3 in Phytochrome-Mediated Light Signaling

Abstract: Plant photoreceptors regulate various developmental processes. Among the photoreceptors, phytochromes, red and far-red light receptors, regulate light responses through many signaling components, including phytochrome-interacting proteins. The functional relationships among phytochromes and their interacting proteins, however, have not been clearly established. Here, we sought to identify a functional relationship between phytochromes and phytochrome interacting factor 3 (PIF3). We demonstrate that PIF3 is pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
163
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(175 citation statements)
references
References 46 publications
11
163
0
1
Order By: Relevance
“…This pattern of light regulation was specifically induced by R but not FR light (Figure 4c). The light-regulated protein abundance of PIF4-HA and PIF5-HA was thus similar to that reported for their close relatives PIF1 and PIF3, except that PIF4 and PIF5 re-accumulated much faster than PIF1 after return into darkness and FR light did not induce a significant decrease in PIF4 and PIF5 (Figure 4c and Supplementary Figure S2c, and data not shown) (Al-Sady et al, 2006;Bauer et al, 2004;Monte et al, 2004;Park et al, 2004;Shen et al, 2005;Viczian et al, 2005).…”
Section: Pif4 and Pif5 Promote The Shade-avoidance Responsesupporting
confidence: 81%
See 2 more Smart Citations
“…This pattern of light regulation was specifically induced by R but not FR light (Figure 4c). The light-regulated protein abundance of PIF4-HA and PIF5-HA was thus similar to that reported for their close relatives PIF1 and PIF3, except that PIF4 and PIF5 re-accumulated much faster than PIF1 after return into darkness and FR light did not induce a significant decrease in PIF4 and PIF5 (Figure 4c and Supplementary Figure S2c, and data not shown) (Al-Sady et al, 2006;Bauer et al, 2004;Monte et al, 2004;Park et al, 2004;Shen et al, 2005;Viczian et al, 2005).…”
Section: Pif4 and Pif5 Promote The Shade-avoidance Responsesupporting
confidence: 81%
“…A similar mechanism operates for PIF3; moreover, PIF3 degradation requires the interaction with phyB through a functional APB domain (Al-Sady et al, 2006). In both cases, the degradation of these transcription factors is proteasome-mediated (Al-Sady et al, 2006;Bauer et al, 2004;Monte et al, 2004;Oh et al, 2006;Park et al, 2004;Shen et al, 2005;Viczian et al, 2005).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The striking constitutively photomorphogeniclike phenotype of quadruple pif1 pif3 pif4 pif5 (pifq) mutant seedlings grown in complete darkness (Leivar et al, 2008a) has provided compelling evidence that these PIF family members function collectively, in a partially redundant or overlapping fashion, to constitutively promote skotomorphogenesis (repress photomorphogenesis) in young dark-grown seedlings (Leivar et al, 2008a;Shin et al, 2009). Additional evidence shows that photoactivated phy reverses this promotion/repression, upon initial exposure to light, by inducing rapid degradation of the PIF molecules, via the ubiquitin-proteasome system (Bauer et al, 2004;Park et al, 2004;Shen et al, 2005Shen et al, , 2008Oh et al, 2006;Nozue et al, 2007;Shen et al, 2007;Lorrain et al, 2008). This process involves rapid, phy-induced phosphorylation of the interacting bHLH protein in the nucleus, as a prelude to ubiquitin-proteasome system-mediated proteolysis (Al-Sady et al, 2006Shen et al, 2007Shen et al, , 2008Lorrain et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These analyses revealed that the individual family members have, at least in part, redundant functions (Castillon et al 2007; Leivar et al 2008). PIF function is also negatively regulated by interactions with light-activated phytochrome B that induce PIF proteolysis in the light (Bauer et al 2004;Park et al 2004;Shen et al 2005). PIFs thus integrate light and GA signals to control developmental responses.…”
mentioning
confidence: 99%